2012
DOI: 10.1039/c2cp40294g
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of Criegee intermediate (CH2OO) reactions with acetone, acetaldehyde, and hexafluoroacetone

Abstract: Criegee biradicals, i.e., carbonyl oxides, are critical intermediates in ozonolysis and have been implicated in autoignition chemistry and other hydrocarbon oxidation systems, but until recently the direct measurement of their gas-phase kinetics has not been feasible. Indirect determinations of Criegee intermediate kinetics often rely on the introduction of a scavenger molecule into an ozonolysis system and analysis of the effects of the scavenger on yields of products associated with Criegee intermediate reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
251
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(289 citation statements)
references
References 42 publications
34
251
3
1
Order By: Relevance
“…Berndt et al (2014a) also showed that significant differences in the relative rate coefficients k(sCI + H 2 O) / k(sCI + SO 2 ) occurred between syn-and anti-confomers of sCI from trans-2-butene. Absolute measurements by Taatjes et al (2012) support this finding as well.…”
Section: Sci Yields and Relative Rate Coefficientssupporting
confidence: 78%
See 2 more Smart Citations
“…Berndt et al (2014a) also showed that significant differences in the relative rate coefficients k(sCI + H 2 O) / k(sCI + SO 2 ) occurred between syn-and anti-confomers of sCI from trans-2-butene. Absolute measurements by Taatjes et al (2012) support this finding as well.…”
Section: Sci Yields and Relative Rate Coefficientssupporting
confidence: 78%
“…Due to the relatively long lifetime of sCI, bimolecular reactions of sCIs with several compounds like water vapour, SO 2 , carbonyls, organic acids, etc., are also possible (e.g. Neeb et al, 1996Neeb et al, , 1997Johnson, 2001;Welz et al, 2012Welz et al, , 2014Mauldin III et al, 2012;Berndt et al, 2012Berndt et al, , 2014aTaatjes et al, 2012Taatjes et al, , 2013. These reactions can potentially be fast enough to contribute significantly to the atmospheric oxidation capacity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3,10] Stabilized CIs react quickly (~10 -12 -10 -10 cm 3 s -1 ) with many trace atmospheric gases. [8,[11][12][13][14] Under humid conditions, reaction with SO2 leads to H2SO4 which catalyzes growth of atmospheric aerosol particles. [4,[15][16][17][18] The steady state concentrations of CIs in the atmosphere are limited by reactions with scavengers, the most important of which is water vapor.…”
mentioning
confidence: 99%
“…Stabilised CIs (SCIs) are known to react with a variety of compounds, including H 2 O, NO 2 , SO 2 , and a variety of organic compounds (e.g. Mauldin III et al, 2012;Taatjes et al, 2012Taatjes et al, , 2013Taatjes et al, , 2014Ouyang et al, 2013;Stone et al, 2014a). There is experimental evidence for the formation of OH from the thermal decomposition of SCIs, on a much longer timescale than the decomposition or isomerisation of excited CIs (Kroll et al, 2001a, b).…”
Section: H M Walker Et Al: Night-time Measurements Of Ho Xmentioning
confidence: 99%